Sinonasal Stent Coated with Slow-Release Varnish of Chlorhexidine Has Sustained Protection against Bacterial Biofilm Growth in the Sinonasal Cavity: An In Vitro Study - Alessandra Cataldo Russomando; Ronit Vogt Sionov; Michael Friedman; Irith Gati; Ron Eliashar; Doron Steinberg; Menachem Gross (MDPI AG, 2021)
The aim of the study was to develop a sustained-release varnish (SRV) containing chlorhexidine (CHX) for sinonasal stents (SNS) to reduce bacterial growth and biofilm formation in the sinonasal cavity. Segments of SNS were coated with SRV-CHX or SRV-placebo and exposed daily to bacterial cultures of Staphylococcus aureus subsp. aureus ATCC 25923 or Pseudomonas aeruginosa ATCC HER-1018 (PAO1). Anti-bacterial effects were assessed by disc diffusion assay and planktonic-based activity assay. Biofilm formation on the coated stents was visualized by confocal laser scanning microscopy (CLSM) and high-resolution scanning electron microscopy (HR-SEM). The metabolic activity of the biofilms was determined using the 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) method. Disc diffusion assay showed that SRV-CHX-coated SNS segments inhibited bacterial growth of S. aureussubsp. aureus ATCC 25923 for 26 days and P. aeruginosa ATCC HER-1018 for 19 days. CHX was released from coated SNS segments in a pH 6 medium up to 30 days, resulting in growth inhibition of S. aureussubsp. aureus ATCC 25923 for 22 days and P. aeruginosa ATCC HER-1018 for 24 days. The MTT assay showed a reduction of biofilm growth on the coated SNS by 69% for S. aureussubsp. aureus ATCC 25923 and 40% for P. aeruginosa ATCC HER-1018 compared to the placebo stent after repeated exposure to planktonic growing bacteria. CLSM and HR-SEM showed a significant reduction of biofilm formation on the SRV-CHX-coated SNS segments. Coating of SNS with SRV-CHX maintains a sustained delivery of CHX, providing an inhibitory effect on the bacterial growth of S. aureussubsp. aureus ATCC 25923 and P. aeruginosa ATCC HER-1018 for approximately 3 weeks.